Preparation and biological evaluation of soluble tetrapeptide epoxyketone proteasome inhibitors. Issue 18 (15th September 2019) - Lei, Meng; Zhang, Haoyang; Miao, Hang; Du, Xiao; Zhou, Hui; Wang, Jia; Wang, Xueyuan; Feng, Huayun; Shi, Jingmiao; Liu, Zhaogang; Shen, Jian; Zhu, Yongqiang
Graphical abstract: Abstract: A series of novel tetrapeptidyl epoxyketone inhibitors of 20S proteasome was designed and synthesized. To fully understand the SAR, various groups at R 1, R 2, R 3, R 4 and R 5 positions, including aromatic and aliphatic substituents were designed, synthesized and biologically assayed. Based on the enzymatic results, seven compounds were selected to evaluate their cellular activities and soluble compound 36 showed strong potency against human multiple myeloma (MM) cell lines. Microsomal stability results indicated that compound 36 was more stable in mice, rat and human microsomes than marketed carfilzomib. The in vivo activities of this compound were evaluated with the xenograft mice models of MM cell lines ARH77 and RPMI-8226 with luciferase expression and the T/C value of the two models were 49.5% and 37.6%, respectively. To evaluate the potential cardiovascular toxicity, inhibition of hERG ion channel in HEK293 cells by compound 36 and carfilzomib was carried out. The results indicated that 36 had no binding affinity for the hERG ion channel while carfilzomib could bind it with IC50 of 92.1 μM.